Hubungan Paritas dengan Anemia pada Ibu Hamil di Rumah Sakit Bhakti Asih - Upi Parida; Fadhila Arienda Humaira (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
Childbirth often results in perineal tears, particularly in first-time deliveries, and can also occur in subsequent births. Improper perineal care can create a moist environment due to lochia, promoting bacterial growth and increasing the risk. Anemia in pregnancy remains a significant health issue in Indonesia, affecting around 67% of pregnant women in 2011, with regional variations. Severe anemia (10-15%) can negatively impact fetal growth and development. In West Jakarta, the anemia rate was 33.9% in 2021, while at the Grogol Petamburan Health Center, it was 5.6%. This study aimed to analyze the relationship between anemia and parity in pregnant women at the Grogol Petamburan Health Center in 2022. A descriptive-analytical study with a cross-sectional approach was conducted on 100 pregnant women attending antenatal care (ANC) from January to March, selected through random sampling. Data were obtained from medical records and analyzed using univariate and bivariate chi-square tests. Results showed that 57% of pregnant women had anemia, with 80% having parity of fewer than four children. The statistical test showed a p-value of 1.000 (>0.05), indicating no significant relationship between anemia and parity. Pregnant women are advised to undergo regular check-ups and maintain balanced nutrition during pregnancy.